What (Doesn't) Make an Heroic Act? - Payton, Jonathan (Stance: an international undergraduate philosophy journal, 2019)
This paper focuses on the nature of saintly or heroic acts, which, according to J.O. Urmson, exist as a fourth, less traditional category of moral actions. According to this division, heroic acts are those, which have positive moral value, but cannot be demanded of an individual as their duty; however, this paper argues that Urmson is mistaken in his claim that a consequentialist ethical framework is the most capable of accounting for heroic acts. Furthermore, this paper claims that an Aristotelian account is the most appropriate ethical theory to consider, which could better countenance the existence of heroic acts.